Free-carrier-induced soliton fission unveiled by in situ measurements in nanophotonic waveguides - Chad Husko (Nature Portfolio, 2016)
Solitons are nonlinear waves that exist in diverse forms of matter. Here, Husko et al. use near-field measurements to observe the spatio-temporal evolution of optical pulses in a nanophotonic semiconductor waveguide, demonstrating that nonlinear photo-carrier generation can induce fission of solitons.